Synthesis and characterization of novel biodegradable crosslinked polyesters - Kanishka Indumati Kumari Herath (2011)
In this work, the synthesis of novel biodegradable crosslinked polyesters was explored via two different methods. The main objective was to obtain soft and elastomeric polymers suitable for future applications in soft tissue engineering. Currently, there are no elastomers on the market meeting the need for both low hysteresis and biodegradability. The first synthetic route to achieving this objective was the photopolymerization of a multifunctional, non-toxic monomer to which biodegradable polymers were attached. Diallyl tartrate was the monomer of choice due to its pendant hydroxyl groups for subsequent polymer incorporation. As there has been no study on it before, the photopolymerizability of diallyl tartrate was first established using differential photocalorimetry and the obtained thermoset was characterized. It was found that the optimum amount of photoinitiator required was 3-4 wt% and samples of diallyl tartrate with thickness of about 2 mm polymerized within 2.5 h with 70 % degree of cure. Both the thermoset and its degradation products were shown to be non-toxic to cells over 24 h. Photopolymerized diallyl tartrate displayed a gradual rate of hydrolytic degradation, losing nearly 50 % of its mass in 3 months. Despite the potential of this material in other bio-applications, its high glass transition temperature of around 90 C and its storage modulus of around 1 GPa deem it not suitable for applications in soft tissue engineering. There were difficulties in obtaining softer, more elastomeric polymers via this synthetic route. The second route of synthesis involved a two-part system: an amine-terminated prepolymer and poly(ethylene glycol) diglycidyl ether (PEG-diglycidyl ether). In this work, two prepolymers were chosen: Poly(caprolactone) (PCL) of molecular weight 3000 g/mol and a random 50/50 copolymer, poly(caprolactone-co-d,l-lactide) of molecular weight 18000 g/mol. These prepolymers were successfully synthesized and characterized. The crosslinkers used for the subsequent crosslinking were PEG diglycidyl ether of two lengths: 500 g/mol and 1000 g/mol. Four different crosslinked polymers of gel contents of 40-50 % by mass were successfully synthesized and characterized. It was found that the longer the PEG crosslinker used, the higher the amount of swelling exhibited and hence the faster the initial rate of hydrolytic degradation.